Shock-wave therapy versus corticosteroid injection on lateral epicondylitis: a meta-analysis of randomized controlled trials. Issue 3 (3rd July 2019) - Xiong, Yuan; Xue, Hang; Zhou, Wu; Sun, Yun; Liu, Yi; Wu, Qipeng; Liu, Jing; Hu, Liangcong; Panayi, Adriana C.; Chen, Lang; Yan, Chenchen; Mi, Bobin; et al.
ABSTRACT: Background : Shock-wave (SW) therapy has been widely promoted and proven to be effective in ameliorating symptoms of lateral epicondylitis (LE) during recent years. Corticosteroid (CS) injection is another common treatment of LE, and several researches have documented its significant effect in the treatment of LE. Despite this, few studies have focused on comparing the use of SW and CS in the treatment of LE. The aim of this meta-analysis is to assess whether SW is superior to CS in managing LE, both in terms of ameliorating pain and improving functionality. Methods : A systematic search of the literature was conducted to identify relevant articles that were published in Pubmed, Medline, Embase, the Cochrane Library, SpringerLink, Clinical Trials.gov and OVID from the databases' inception to December 2018. All studies comparing the efficacy of SW and CS in terms of pain levels and functionality improvement were included. Data on the two primary outcomes were collected and analyzed using the Review Manager 5.3. Results : Four studies were included in the current meta-analysis. A significant difference in VAS score (SMD = 1.13, Cl 0.72−1.55 P < 0.00001, I 2 = 0) was noted between the SW group and the CS group. Furthermore, Significant difference was also seen in the term of grip strength (including HGS and GSS scoring system) (SMD = -1.42, Cl -1.85−-0.98 P < 0.00001, I 2 = 0). Conclusions : In light of the better improvement in the terms of VAS and grip strength with follow-up more than 12 weeks, we assume that SW may be a superior alternative for the treatment of LE.